1992
DOI: 10.1152/jn.1992.68.6.2199
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of burst and tonic responses to the receptive field properties of lateral geniculate neurons in the cat

Abstract: 1. In an anesthetized, paralyzed in vivo preparation, we recorded extracellular responses of 61 geniculate neurons (2 W, 25 X, 33 Y, and 1 mixed) to drifting sine-wave gratings of various spatial frequency, temporal frequency, and contrast. Our goal was to study the differential contributions to these visual responses of bursting caused by voltage dependent, low-threshold (LT) Ca2+ spikes and of purely tonic responses unrelated to LT spikes. Cells responding with LT spikes are said to be in the burst firing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
167
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(183 citation statements)
references
References 29 publications
15
167
0
Order By: Relevance
“…First, our estimates of bursting are based on spontaneous activity. Prior studies of the lateral geniculate nucleus (9) have shown that levels of spontaneous activity are much lower during burst mode than during tonic mode. That is, when in burst mode, a thalamic relay cell is often silent, and thus this period cannot be judged to be any particular firing mode, but such a silent neuron challenged with a visual stimulus will often respond with a burst.…”
Section: Extent Of Burstingmentioning
confidence: 85%
See 1 more Smart Citation
“…First, our estimates of bursting are based on spontaneous activity. Prior studies of the lateral geniculate nucleus (9) have shown that levels of spontaneous activity are much lower during burst mode than during tonic mode. That is, when in burst mode, a thalamic relay cell is often silent, and thus this period cannot be judged to be any particular firing mode, but such a silent neuron challenged with a visual stimulus will often respond with a burst.…”
Section: Extent Of Burstingmentioning
confidence: 85%
“…This firing mode strongly affects the nature of the signal that is relayed to the cortex (4). For example, compared with tonic mode, burst mode produces much more nonlinear distortion in the relay of information, but the information relayed has greater detectability because of a greater signal-to-noise ratio and stronger activation of postsynaptic cortical targets (4)(5)(6)(7)(8)(9). From these properties, the hypothesis has been forwarded that burst firing, with its greater detectability and cortical activation, serves as a ''wake-up call'' to the cortex that there has been a change in the outside world (e.g., a novel stimulus within the receptive field of a relay cell for one of the sensory thalamic nuclei); tonic mode, with its more linear relay of information, is then better suited for a more faithful analysis of the relayed information (4,7).…”
mentioning
confidence: 99%
“…First, burst firing acts as an effective relay and amplifying signal in vivo [68][69][70][71]. Burst firing performs better signal detection [70,72], effectively relays auditory information in a non-linear input-output manner, regulates the frequency selectivity of MGB neurons [70,73,74], and may be involved in the generation of oscillations [75,76]. Second, RD and rebound spikes may be directly responsible for neuronal off-responses [8,77,78], which are shown by MGB neurons [79,80].…”
Section: Kir Channels Regulate Rd By Changing the Resting Membrane Pomentioning
confidence: 99%
“…There is, however, evidence for the presence of bursts in the thalamus of awake animals (Guido et al 1992;Guido & Weyand 1995;Sherman 2001). The thalamic bursts may convey a special type of information in alert states, such as novelty detection (Sherman 2001).…”
Section: Introductionmentioning
confidence: 99%